Corporate Readiness for Enlargement in Central Europe - Zlatan Fröhlich (European Regional Science Association (ERSA), 2003)
Enlarging the Union is one of the most important challenges for Europe in this new millennium. Its impact stretches the simple extension of the Single Market, but calls for a revision of all European Union policies, procedures and beyond organisation. It is imperative therefore to involve governments, civil society and business community in this process, to ensure that enlargement is well understood and accepted by all. The CAPE 2002 survey, organised with support of the EU Phare programme, is a vital instrument in this strategy. This survey on corporate readiness for the EU Single Market in the 10 Candidate Countries of Central Europe plus Croatia (which will apply for the candidate status in 2003) is the second systematic survey conducted among companies in the region. The survey illustrates what enterprises in the Central European Candidate Countries really think about the enlargement, how they assess and anticipate its consequences, and how they prepare for it. The companies responded to 21 questions in the following 3 areas: ?information on and compliance with the Acquis', ?corporate strategies and attitude to Accession? and ?the Accession process and lobbying in Brussels'. Percentages of answers given by respondents to most questions were relatively high, which demonstrates a growing interest and awareness of the corporate sector in Candidate Countries in EU matters, and its commitment to early accession. In this paper will be given an overview of survey and discuss main results which are revealing in many ways and call for action: action by governments and by the enterprises themselves.
Keywords: 330